Magnetohydrodynamic Waves in Multi-Layered Asymmetric Waveguides: Solar Magneto-Seismology Theory and Application - Allcock, Matthew; Shukhobodskaia, Daria; Zsámberger, Noémi Kinga; Erdélyi, Robert (Frontiers in Astronomy and Space Sciences, 2019)
Diagnosing the solar atmospheric plasma is one of the major challenges in solar physics. Magnetohydrodynamic (MHD) waves, by means of applying the powerful concept of solar magneto-seismology (SMS), provide a tool to obtain diagnostic insight into the magnetised solar plasma in MHD waveguides. This paper provides a road-map of simple but applicable models of solar atmospheric waveguides in the framework of Cartesian geometry. We focus on exploiting the diagnostic potential of waveguide asymmetry and consider the effects of steady flow. In particular, the dispersion relation describing linear MHD wave propagation along a multi-layered MHD waveguide is derived. Aiming at lower solar atmospheric applications of SMS, the special case of a single magnetic slab embedded in an asymmetric magnetised plasma environment is revisited. As a proof of concept, the Amplitude Ratio Method is used to make a seismological estimate of the local Alfvén speed in several chromospheric fibrils that exhibit asymmetric oscillations. Absolute ratios of boundary oscillations between 1.29 and 3.42 are detected and, despite the significant errors expected, the local Alfvén speed estimates agree with previously derived estimates from magnetic field extrapolations. Finally, the effects of asymmetric shear flows present in these slab MHD waveguides are considered as a suitable model of Kelvin-Helmholtz instability initiation that is applicable, for example, to coronal mass ejection flanks.